(untitled) (Revista de Ciências Agroveterinárias, 2004)
Final plant density in cassava, being a function o sprouting emergency, is a limitant factor for root yield, what depends on the quality of stem cutting. This work was conducted to evaluate the effect of the stem cutting length on emergency and root yield of cassava. Two experiments were carried out: the first one in Glorinha, where the treatments was the cultivar Paraguaia with stem cutting length of 10 and 20 cm and the cultivar RS 14 with 20 cm and the second experiment was conducted in Eldorado do Sul, where the treatments were the Apronta a Mesa cultivar with stem cutting of 5,10,15 and 20 cm. In the second experiment, to avoid a lack of plant density uniformity, was increase the number of stem cutting in the treatments of 5 and 10 cm increased, and plant density adjusted 60 days after sowing by removal of plant excess. The sprouting emergency, in the two experiments, varied as a function of cultivar and stem cutting length. The reduction of emergency in the experiment with Paraguaia cultivar was 70,8% lower in the treatment with 10 cm in relation to 20 cm. In the Apronta a Mesa cultivar there was not difference in this characteristic in the treatment of 15 and 20 cm. The reductions of stem cutting length to 5 and 10 cm, reduced the emergency in 54,7 and 29,2%, respectively. The highest cassava root yield, in the trial of Glorinha, was observed in the treatments with stem cutting of 20 cm, independently of cultivar, while in Eldorado do Sul the differences among the treatments were not significant, because it was used, in this experiment, similar plant density in all treatments. The main effect of reduction of stem cutting length is the reduction of sprouting emergence and plant density, with decrease of the cassava root yield.